COVID-19 Vaccines Safety Tracking (CoVaST): Protocol of a Multi-Center Prospective Cohort Study for Active Surveillance of COVID-19 Vaccines' Side Effects - Riad, Abanoub; Schünemann, Holger; Attia, Sameh; Peričić, Tina Poklepović; Žuljević, Marija Franka; Jürisson, Mikk; Kalda, Ruth; Lang, Katrin; Morankar, Sudhakar; Yesuf, Elias Ali; Mekhemar, Mohamed; Danso-Appiah, Anthony; et al. (International journal of environmental research and public health, 2021)
BACKGROUND: Coronavirus disease (COVID-19) vaccine-related side effects have a determinant role in the public decision regarding vaccination. Therefore, this study has been designed to actively monitor the safety and effectiveness of COVID-19 vaccines globally. METHODS: A multi-country, three-phase study including a cross-sectional survey to test for the short-term side effects of COVID-19 vaccines among target population groups. In the second phase, we will monitor the booster doses' side effects, while in the third phase, the long-term safety and effectiveness will be investigated. A validated, self-administered questionnaire will be used to collect data from the target population; Results: The study protocol has been registered at ClinicalTrials.gov, with the identifier NCT04834869. CONCLUSIONS: CoVaST is the first independent study aiming to monitor the side effects of COVID-19 vaccines following booster doses, and the long-term safety and effectiveness of said vaccines.
Keywords: cross-sectional studies; SARS-CoV-2; vakcíny; mass vaccination; průřezové studie; pozorné vyčkávání; lidé; drug-related side effects and adverse reactions; vakcíny proti COVID-19; COVID-19; Vaccines; Humans; prevalence; prospektivní studie; Cross-Sectional Studies; Prospective Studies; cohort studies; health personnel; COVID-19 Vaccines; Watchful Waiting